Surface Modification for Promoting Durable, Efficient, and Selective Electrocatalysts. Issue 11 (21st April 2020) - Lenne, Quentin; Leroux, Yann R.; Lagrost, Corinne
Abstract: Intensive research into the design of catalysts involved in energy conversion and fuel cell technologies has allowed great progress in the field. However, durable, efficient and selective electrocatalytic systems for the activation of fuel molecules at the lowest cost are still needed. The most developed strategies consist of tailoring the shape, size and composition of metallic nanomaterials. Yet, deliberate surface modification of the catalysts should be considered as a promising alternative approach. The functionalization of metallic catalysts with organic ligands has been recently demonstrated to promote high catalytic activity. This Review focuses on the functionalization of metallic or alloy catalysts with organic ligands, showing the impact of the surface modification for different materials and different reactions. Hybrid systems based on this alternative strategy could contribute to the elaboration of cutting‐edge systems for electrocatalysis. Abstract : Yin and yang : A tale of synergy between organic ligands and metallic catalysts.